Local partnerships for rural development [ the European experience - Moseley, Malcolm J. (CABI, 2003)
Annotation This book has been developed from a report of the cross-national PRIDE (Partnerships for Rural Integrated Development in Europe) research project. The research involved focusing on public and private sector rural development experience of sixember states of the European Union, namelyFinland, Germany, Italy, Spain, Sweden and the UK.